Translation in the Zone of the Dubash: Colonial Mediations of Anuvāda. Issue 1 (14th February 2017) - Hatcher, Brian A.
Abstract : Responding to recent critical reflection on the concept of anuvāda within the fields of translation studies and South Asian literary cultures, this article explores the complex colonial mediations shaping modern Bengali understandings of the term. The goal is to situate the production of new meanings of anuvāda within the zone of the Dubash, a phrase used here to conjure the highly mediated space of vernacular translation as practiced by Bengali intellectuals under colonial rule. This article argues that if we wish to employ anuvāda as a tool for rethinking the meaning and practice of translation, we must first attend to the processes that transformed the norms and goals of textual transmission in the colonial era. In the end we can hope not only to enrich our understanding of South Asian translational practices but also to appreciate the role played by translation in the story of literary modernity in Bengal.